Families Experience and Deal With Palliative Care Provided To Their Family Members - Nilawati Nilawati; Rados Kristian Nazara (International Journal Of Health Science, 2024)
This study aims to explore the experiences of families who have members undergoing palliative care. Using a phenomenological approach, we conducted in-depth interviews with six families involved in home palliative care. Data were analyzed using Colaizzi analysis to identify the main themes that emerged from the family's experiences. The study results show that families' experiences with palliative care patients are complex and emotionally charged. The main themes that emerged included: 1) Family emotional feelings, 2) Family obstacles in facing the treatment process and 3) Family support. This study provides in-depth insight into families' experiences with palliative care patients, highlighting the complexities, challenges, and needs involved in caring for an ill family member. Clinical implications of these findings include the importance of supporting families with appropriate resources and services, improving family communication and engagement in care, and recognizing the importance of emotional and social support in strengthening family well-being throughout the palliative care journey.